STUDENTS’ PROBLEMS IN SPEAKING ENGLISH LANGUAGE AT THE NINTH GRADE OF SMP NEGERI 1 O’O’U - Giawa, Amator Andisinarta (Research on English Language Education, 2025)
This research was conducted to investigate students' problems in speaking English in the ninth grade of SMP Negeri 1 O’o’u. The objectives of this research were to find what are students problems in speaking English at the ninth grade of SMP negeri 1 O’o’u and what are factors cause the problems faced by students in problems speaking English at the ninth grade of SMP Negeri 1 O’o’u. This research was applied in a qualitative research design and the data were obtained through classroom observations and interviews. Data were analyzed using Miles and Huberman's theory such as data reduction, data display, and drawing conclusions and verification. The results of this research indicate that ninth grade students at SMP Negeri 1 O’o’u experience problems in speaking English. It was found that 4 negative characteristics of successful speaking activity are experienced by students, namely student didn’t talk a lot, participant or students are not even, student low motivation and language is not of an acceptable level. Factors that cause students' problems in speaking English include fear of mistakes, shyness, anxiety, lack of confidence and lack of motivation. This research show that students experience problem in speaking. It is suggested that students ninth grade of SMP Negeri 1 O’o’u should study more the characteristic successful speaking activity